Family and social vulnerability: a study with octogenarians La familia y la vulnerabilidad social: un estudio con octogenarios Família e vulnerabilidade social: um estudo com octogenários - Sofia Cristina Iost Pavarini; Elizabeth Joan Barha; Marisa Silvana Zazzetta de Mendiondo; Carmen Lucia Alves Filizola; José Fernando Petrilli Filho; Ariene Angelini dos Santos (Universidade de São Paulo, 2009)
In order to guide the development of dementia-related public policies for the elderly, it is important to identify factors that vary together with the social vulnerability of this population. This study aimed to identify the relationship between the São Paulo Social Vulnerability Index (IPVS) and various indicators of family support for elderly people over 80 years of age, who presented cognitive alterations (N=49). All ethical guidelines were followed. Data were collected at the homes of the elderly people. A large majority of the respondents lived with family members (88%). In half of the cases, the respondents lived with one (41%) or two (9%) other elderly persons. On average, there was one more non-elderly person living in the high vulnerability family context (M = 3.6, sd = 1.70) than in contexts of very low vulnerability (M = 2.4, sd = 1.07), F(2.43) = 3.364, p < 0.05. However, the functionality of the support provided by these family members needs to be verified, in each of these contexts. Para elaborar políticas públicas para el cuidado de anciano con demencia, es importante verificar factores que varían con la vulnerabilidad social de esa población. El objetivo de este estudio fue identificar la relación entre una medida de vulnerabilidad social (IPVS) y algunos indicadores de apoyo familiar para ancianos, con más de 80 años, con alteraciones cognitivas (N=49). Todas las recomendaciones éticas fueron observadas. Los datos fueron recolectados en los domicilios de los ancianos. La gran mayoría de los entrevistados vivía con la familia (88%). En la mitad de las familias los ancianos vivían con uno (41%) o dos ancianos (9%). En promedio había una persona más, que no era anciana, viviendo en el contexto familiar de alta vulnerabilidad (M=3,6, DE=1,70) que en el contexto de muy baja vulnerabilidad (M=2,4, DE=1,07), F (2, 43)=3,364, p<0,05. Sin embargo, es necesario verificar la funcionalidad del apoyo familiar en esos contextos. Para direcionar políticas públicas para cuidado ao idoso com demência, é importante verificar fatores que variam com a vulnerabilidade social dessa população. O objetivo foi identificar a relação entre uma medida de vulnerabilidade social (IPVS) e alguns indicadores de apoio familiar para idosos acima de 80 anos, com alterações cognitivas (N=49). Todos os cuidados éticos foram observados. Os dados foram coletados nos domicílios dos idosos. A grande maioria dos entrevistados morava com a família (88%). Em metade das famílias os idosos moravam com mais um (41%) ou dois idosos (9%). Em média havia uma pessoa a mais, não idosa, morando no contexto familiar de alta vulnerabilidade (M=3,6, dp=1,70) do que no contexto de muito baixa vulnerabilidade (M=2,4, dp=1,07), F (2, 43)=3,364, p<0,05. Porém, há necessidade de verificar a funcionalidade do apoio familiar nesses contextos.